ANALYSIS OF FINANCIAL STATEMENT RATIO AT PT BANK BRI SYARIAH TBK ACCORDING TO ISLAMIC PERSPECTIVE - Aprillia Dwi Fatma; Nana Diana (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2021)
This research was conducted to determine the ratio analysis of financial statements at PT Bank BRI Syariah Tbk, namely through profitability ratios. This research uses ratio analysis methodology, which is to analyze using comparisons of quantitative data shown in the balance sheet and profit and loss. . Data obtained from Bank BRI Syariah’s financial statements in Indonesia Stock Exchange, namely for three consecutive years, from 31 December 2017 to 31 December 2019. From this study, the results showed that the Net Profit Margin in 2017 was 5.67%, in 2018 it was 5.39%, and in 2019 it was 3.21%. Return on assets in 2017 was 0.32%, in 2018 it was 0.28%, and in 2019 it was 0.17%. Return On Equity in 2017 was 3.88%, in 2018 was 2.12%, and in 2019 was 1.45%. The development of the level of profitability at PT Bank BRI Syariah Tbk in 2017 - 2019 has decreased every year.